The hypotyresis in patients with chronic obsructive pulmonary disease (COPD) - Matsegora, N. A.; Shpota, O. E. (Journal of Education, Health and Sport, 2018)
The processes of reparative regeneration of the bronchial epithelium are controlled by thymic factors, thyroid hormones, and cellular immunity in patients with COPD in a stage of exacerbation. It complicates by purulent necrotic of the bronchopulmonary system amid a decrease of reduce synthesis of endogenous triiodothyronine. We gave pathophysiological rationale for use of thyroid hormone replacement therapy for correction of hormone (thymalin and thyroid -) dependent functional activity of lymphocytes. We proved the clinical effectiveness of the using alternative triiodothyronine therapy as an extra-immune immunocorrector. It includes thyroid and thymalin-dependent effects in patients with COPD with low triiodothyronine syndrome in the period of exacerbation.